Anal sac disease in dogs. Issue 9 (1st October 2015) - Rutherford, Lynda; Lee, Karla
Abstract : Anal sac disease (ASD) can be divided into two main categories: inflammation and neoplasia. It is relatively common in dogs, with the inflammatory form having a reported prevalence of 12.5 per cent. Cases of ASD present with signs of perineal pruritus such as licking, scooting and tail base discomfort, as well as dyschezia and tenesmus. This article discusses the most common anal sac conditions seen in veterinary practice, and describes how they can be managed, both medically and surgically.